Iron-doxorubicin prodrug loaded liposome nanogenerator programs multimodal ferroptosis for efficient cancer therapy - Yinxian Yang; Shiyi Zuo; Linxiao Li; Xiao Kuang; Jinbo Li; Bingjun Sun; Shujun Wang; Zhonggui He; Jin Sun (Elsevier, 2021)
Ferroptosis is a new mode of cell death, which can be induced by Fenton reaction-mediated lipid peroxidation. However, the insufficient H2O2 and high GSH in tumor cells restrict the efficiency of Fenton reaction-dependent ferroptosis. Herein, a self-supplying lipid peroxide nanoreactor was developed to co-delivery of doxorubicin (DOX), iron and unsaturated lipid for efficient ferroptosis. By leveraging the coordination effect between DOX and Fe3+, trisulfide bond-bridged DOX dimeric prodrug was actively loaded into the core of the unsaturated lipids-rich liposome via iron ion gradient method. First, Fe3+could react with the overexpressed GSH in tumor cells, inducing the GSH depletion and Fe2+generation. Second, the cleavage of trisulfide bond could also consume GSH, and the released DOX induces the generation of H2O2, which would react with the generated Fe2+in step one to induce efficient Fenton reaction-dependent ferroptosis. Third, the formed Fe3+/Fe2+ couple could directly catalyze peroxidation of unsaturated lipids to boost Fenton reaction-independent ferroptosis. This iron-prodrug liposome nanoreactor precisely programs multimodal ferroptosis by integrating GSH depletion, ROS generation and lipid peroxidation, providing new sights for efficient cancer therapy.